2020
DOI: 10.1111/ene.14516
|View full text |Cite
|
Sign up to set email alerts
|

Transesophageal Echocardiography – Dysphagia Risk in Acute Stroke (TEDRAS): a prospective, blind, randomized and controlled clinical trial

Abstract: Background and purpose: Dysphagia is common in acute stroke and leads to worse overall outcome. Transesophageal echocardiography (TEE) is used in the diagnostic evaluation of stroke with regard to its etiology and is a known cause of postoperative dysphagia in cardiac surgery. The prevalence of dysphagia in acute stroke patients undergoing TEE remains unknown. The aim of the Transesophageal Echocardiography-Dysphagia Risk in Acute Stroke (TEDRAS) study was to assess the influence of TEE on swallowing among pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Previous studies (11)(12)(13)) have shown that intermittent tube feeding can be used as an alternative to the traditional indwelling nasogastric tube. It is not only a way of nutritional support, but also an intervention for the treatment of dysphagia, which can improve nutritional status and swallowing function (14). However, some studies have shown that compared with continuous indwelling nasogastric tube, the effect of intermittent tube feeding in improving nutrition, swallowing function is not significant (15), so the effect of intermittent tube feeding in stroke dysphagia is still controversial.…”
Section: Original Articlementioning
confidence: 99%
“…Previous studies (11)(12)(13)) have shown that intermittent tube feeding can be used as an alternative to the traditional indwelling nasogastric tube. It is not only a way of nutritional support, but also an intervention for the treatment of dysphagia, which can improve nutritional status and swallowing function (14). However, some studies have shown that compared with continuous indwelling nasogastric tube, the effect of intermittent tube feeding in improving nutrition, swallowing function is not significant (15), so the effect of intermittent tube feeding in stroke dysphagia is still controversial.…”
Section: Original Articlementioning
confidence: 99%
“…Still, emergent cardiac CT imaging in acute stroke could be beneficial due to the direct detection of intra-cardiac thrombi in close temporal proximity to the event compared to echocardiography, which is often delayed by several days in clinical practice, and might fail to demonstrate thrombus due to thrombolytic processes 6 . Particularly TEE can frequently not be performed in acute stroke patients due to its semi-invasive nature, the need for sedation and the prevalence of relative contraindications as dysphagia 17 .…”
Section: Discussionmentioning
confidence: 99%
“…6,14 Transesophageal echocardiogram (TEE), which offers gold standard visualization of the LA/LAA, is invasive, not widely available due to resource constraints, 14,15 and may exacerbate dysphagia in stroke patients. 16 Cardiac CT angiography (cCTA) is a potential alternative imaging modality to assess cardiac structures and address some of the limitations of echocardiogram. ECGgated cCTA has been investigated for the detection of LA/ LAA thrombus, showing comparable sensitivity and specificity to TEE, but may be challenging to practically implement in the hyperacute setting.…”
Section: Introductionmentioning
confidence: 99%
“…6,14 Transesophageal echocardiogram (TEE), which offers gold standard visualization of the LA/LAA, is invasive, not widely available due to resource constraints, 14,15 and may exacerbate dysphagia in stroke patients. 16…”
Section: Introductionmentioning
confidence: 99%